Towards the Semiotics of (In)sincerity (A Few Preliminary Remarks) - Lotman, Mihhail (Recherches sémiotiques / Semiotic Inquiry, 2015)
Simply stated, sincerity is an intention to express the truth, while insincerity is an intention to mislead. A sincere person can be wrong and give false information, while an insincere person can make a mistake and speak the truth. Sincerity – and not the truth – is what is detected with a polygraph (a mentally ill person responding to the question “Are you Napoleon?” with a negation may well register as lying on a polygraph test).In this paper I bring different examples (from texts which belong to various spheres of discourse) that illustrate a splitting of consciouscess in an otherwise mentally sane person : fantastic accusations (both self-accusations and accusations of others) are presented in a state of both belief and disbelief. Usual triggers for this phenomenon are fear and anger (which often occur together), but reasons may also be found in erotic desire or else in aesthetic licence, etc.